The methodology of the electrical conductivity test for Carthamus tinctorius L. seeds - Ingrid M. H. de L. e Silva; Givanildo Z. da Silva; Mirelle V. Coelho; Gabriela F. Gama; Amalia A. S. Silva; Carla G. Machado (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The electrical conductivity test stands out for generating quick responses for lot differentiation; however, studies are needed to improve this practice in safflower seeds. This study aimed to verify the efficiency and establish a methodology of the electrical conductivity test for safflower seeds. Initially, 12 lots were characterized regarding physical properties and physiological potential. For electrical conductivity, the experiment was carried out in three stages with the 12 lots: firstly, the soaking period was determined (2, 4, 6, 8, and 16 hours), then the volume was evaluated (50, 75, 100, 150, and 200 mL), and finally the number of seeds (25 and 50 seeds) was determined. The electrical conductivity test using 25 seeds in 50 mL of distilled water for six hours of soaking enables the differentiation of safflower seed lots. Multivariate analysis of principal components is efficient in discriminating the vigor of safflower seed lots.